Therapeutic Potential of Adipose Stem Cell-Derived Conditioned Medium on Scar Contraction Model - Yukiko Imai; Nobuhito Mori; Yuma Nihashi; Yutaro Kumagai; Yoichiro Shibuya; Junya Oshima; Masahiro Sasaki; Kaoru Sasaki; Yukiko Aihara; Mitsuru Sekido; Yasuyuki S. Kida (Biomedicines, 2022)
Scars are composed of stiff collagen fibers, which contract strongly owing to the action of myofibroblasts. To explore the substances that modulate scar contracture, the fibroblast-populated collagen lattice (FPCL) model has been used. However, the molecular signature of the patient-derived FPCL model has not been verified. Here, we examined whether the patient-derived keloid FPCL model reflects scar contraction, analyzing detailed gene expression changes using comprehensive RNA sequencing and histological morphology, and revealed that these models are consistent with the changes during human scar contracture. Moreover, we examined whether conditioned media derived from adipose stem cells (ASC-CM) suppress the scar contracture of the collagen disc. Detailed time-series measurements of changes in disc area showed that the addition of ASC-CM significantly inhibited the shrinkage of collagen discs. In addition, a deep sequencing data analysis revealed that ASC-CM suppressed inflammation-related gene expression in the early phase of contraction; in the later phase, this suppression was gradually replaced by extracellular matrix (ECM)-related gene expression. These lines of data suggested the effectiveness of ASC-CM in suppressing scar contractures. Therefore, the molecular analysis of the ASC-CM actions found in this study will contribute to solving medical problems regarding pathological scarring in wound prognosis.